Hypoxia Inducible Factor1α in Correlation with Preeclampsia - Juarsa, Hendrik; Tendean, Hermie M M; Wantania, John E (Indonesian Journal of Obstetrics and Gynecology, 2016)
Objective: To know the correlation between Hypoxia Inducible Factor (HIF)-1α level with preeclampsia. Method: The study was conducted at the Obstetrics and Gynecology Department of Prof. Dr. R. D. Kandou Hospital. This research was carried out from April to June 2014. This study is a cross-sectional analytic approach in preeclampsia and normotensive pregnancy. We perform cubital venous blood sampling for inspection by 5 ml of serum and stored it in a refrigerator (-20°C). The level of HIF-1α serum was done by quantitative ELISA method in Prodia Lab Jakarta. Result: Seventy six pregnant women with 38 normotensive pregnancies and 38 preeclampsia, showed a significant association between the average levels of HIF-1α in the serum of pregnant women with preeclampsia compared to normotensive pregnancies (p = 0.000). Conclusion: There is a positive relationship between the levels of HIF-1α in serum of preeclampsia, in which HIF-1α levels in preeclampsia was higher than normotensive pregnancies. [Indones J Obstet Gynecol 2016; 1: 19-22] Keywords: hypoxia inducible factor-1α, preeclampsia